2009
DOI: 10.1371/journal.pone.0006063
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Food Intake in Drosophila

Abstract: Measurement of food intake in the fruit fly Drosophila melanogaster is often necessary for studies of behaviour, nutrition and drug administration. There is no reliable and agreed method for measuring food intake of flies in undisturbed, steady state, and normal culture conditions. We report such a method, based on measurement of feeding frequency by proboscis-extension, validated by short-term measurements of food dye intake. We used the method to demonstrate that (a) female flies feed more frequently than ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
211
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(226 citation statements)
references
References 39 publications
15
211
0
Order By: Relevance
“…S1A). This result cannot be explained by increased consumption of the DDT-dosed food by the DR flies, because DR flies do not differ from fully fed flies in food intake (19,20). This finding demonstrates that DDT resistance is not necessary for increased longevity and is associated only with particular interventions that extend lifespan.…”
Section: Resultsmentioning
confidence: 83%
“…S1A). This result cannot be explained by increased consumption of the DDT-dosed food by the DR flies, because DR flies do not differ from fully fed flies in food intake (19,20). This finding demonstrates that DDT resistance is not necessary for increased longevity and is associated only with particular interventions that extend lifespan.…”
Section: Resultsmentioning
confidence: 83%
“…As a more sensitive evaluation of relative preferences, we carried out a two-choice drinking assay, which has the advantage of allowing a direct comparison of the ingestion of two taste solutions presented simultaneously (16). This assay measures relative ingestion as an indirect measure of relative preference; however, previous studies have shown that there is a strong correlation between frequency of proboscis extension and ingestion (17). At 100 mM concentrations, flies preferred maltose over fructose and fructose over glucose ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Female Drosophila consume approximately 3 times as much food as their male counterparts, have a much larger gut, and have more stem cells in their digestive tract (Wong et al, 2009). It was confirmed that during the 8h H 2 O 2 pre-treatment, male flies consumed considerably less of the sucrose/H 2 O 2 solution than did female flies, and this might mean that male flies have a lower exposure to the adaptive dose of H 2 O 2 and so are less responsive to H 2 O 2 pretreatment (supplementary material Fig.S1).…”
Section: Role Of the 20s Proteasome In H 2 O 2 -Induced Adaptation Inmentioning
confidence: 99%